Definition of C282Y mutation in a hereditary hemochromatosis family from Turkey - Oya YÖNAL,; Özden HATIRNAZ,; Filiz AKYÜZ,; Gupse KÖROĞLU,; Uğur ÖZBEK,; Kıvanç ÇEFLE,; Zeynel MUNGAN, (Turkish Journal of Gastroenterology, 2019)
-